1998
DOI: 10.3102/00028312035004607
|View full text |Cite
|
Sign up to set email alerts
|

Equity Issues in Collaborative Group Assessment: Group Composition and Performance

Abstract: This study investigated the effects of group ability composition on group processes and outcomes in science performance assessments. Students in 21 eighth-grade science classes worked on science assessments first individually, then in groups, and finally individually again. Group composition had a major impact on group discussion quality and on student achievement. Groups with above-average students produced more accurate and high-quality answers and explanations about how to solve the test problems than group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
63
0
3

Year Published

2001
2001
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 193 publications
(71 citation statements)
references
References 19 publications
5
63
0
3
Order By: Relevance
“…On the other hand, the study also shows that students with lower abilities made greater progress than those with higher abilities. This finding is consistent with observations that although high-ability students can perform equally well in various groups (Webb et al 1998;Dembo and McAuliffe 1987;Hooper and Hannafin 1998;Lundstrom and Baker 2009), they may be held up when grouped with weaker students (Mills and Durden 1992). Among the three groups, Group C was the weakest, but when they worked with Group A and B, they made the greatest progress in the long run.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…On the other hand, the study also shows that students with lower abilities made greater progress than those with higher abilities. This finding is consistent with observations that although high-ability students can perform equally well in various groups (Webb et al 1998;Dembo and McAuliffe 1987;Hooper and Hannafin 1998;Lundstrom and Baker 2009), they may be held up when grouped with weaker students (Mills and Durden 1992). Among the three groups, Group C was the weakest, but when they worked with Group A and B, they made the greatest progress in the long run.…”
Section: Resultssupporting
confidence: 92%
“…More and more researchers support diversity in groups with the hope that stronger students can help weaker ones and will benefit from the experience of tutoring (Webb et al 1998;Dembo and McAuliffe 1987;Hooper and Hannafin 1998). They also found that high-ability students will perform equally well whether in heterogeneous groups or in homogeneous groups.…”
Section: Peer Collaborationmentioning
confidence: 88%
“…Consistent with the mixed opinions regarding the relative superiority of heterogeneous versus homogeneous teams, the empirical research offers mixed findings, with some studies indicating that heterogeneous groupings lead to better achievement for both low-and high-ability students (e.g., Beane & Lemke, 1971;Larson et al, 1984;Webb, 1980), and other studies indicating that low-ability students benefit from heterogeneous groupings, while the achievement of high-ability students suffers (Dar & Resh, 1986;Hooper & Hannafin, 1988;Webb et al, 1998). With respect to heterogeneous groupings, researchers have also suggested that the benefits for low-ability students are significantly larger than the losses incurred by high-ability students (Dar & Resh, 1986;Webb et al, 1998).…”
Section: Ability-based Pairing Strategies and Individual Learningmentioning
confidence: 78%
“…With respect to heterogeneous groupings, researchers have also suggested that the benefits for low-ability students are significantly larger than the losses incurred by high-ability students (Dar & Resh, 1986;Webb et al, 1998). In fact, recent metaanalyses of field studies in cooperative learning (Lou, Abrami, & Spence, 2000;Lou et al, 1996) have shown that the achievement of low-ability students increases by approximately one-half a standard deviation in heterogeneous groupings compared to homogeneous groupings, while the achievement of high-ability students is not differentially influenced by composition strategy.…”
Section: Ability-based Pairing Strategies and Individual Learningmentioning
confidence: 93%
See 1 more Smart Citation